Implementation Of Midwives' Duties In Assisting Childbirth Related To Health Law In The Independent Practice Of Midwives Siska Damayanti, S.ST Bengkulu City - Ayudiah, Febra; Putri, Yesi; sari, Liya Lugita (Journal of Multidisciplinary Research, 2025)
Indonesia has done better in reducing infant and under-five mortality. maternal mortality, the fourth goal of the MDGs. The maternal mortality rate, estimated at around 228 per 100,000 live births, has remained high above 200 for the past decade. Midwives represent great potential for health human resources, but their existence has not been supported by comprehensive legislation. Midwives provide continuous and comprehensive midwifery services with a focus on preventive aspects, and midwives play a role in providing delivery assistance who have the knowledge, skills and abilities to provide safe and clean assistance, handle certain emergency situations to optimise maternal health. Based on that background, the author wants to conduct legal research on ‘Implementation of Midwife Duties in Childbirth Associated with Health Law at Independent Midwife Services’. Siska Damayanti Practice, S.ST Bengkulu Kota’. The formulation of the problem in this study is How is the Implementation of Midwives' Duties in Assisting Childbirth at Siska's Independent Practice Midwife and How is Health Law Related to Childbirth Assistance in Independent Practice Midwives. In this study the authors used normative juridical research or normative legal research, this research data collection technique is secondary and primary research. The conclusion in this study is that the role of midwives in assisting childbirth is very important from the midwife's point of view, because she is related to the legal question which provides authority for all actions taken by midwives. Midwives as health workers whose midwifery practice permits are regulated in Permenkes no 28 of 2017 concerning Permits for Midwifery Practice, midwives are given the authority to assist childbirth.